Dosimetric evaluation of a novel automated noncoplanar volumetric modulated arc therapy technique for treating optic nerve sheath meningiomas - Xiong, Zhenyu; Cheng, Chingyun; Zhou, Lili; Eckroate, Brett; Bell, Loren; Warburton, Fredrick; Huang, David; Motwani, Sabin B.; Cathcart, Charles S.; Nie, Ke; Yue, Ning; Zhang, Yin (Frontiers in Oncology, 2025)
PurposeThis study aimed to evaluate the dosimetric outcomes for the target and organs at risk (OARs) in patients with optic nerve sheath meningiomas (ONSMs), comparing HyperArc (HA), a novel automated noncoplanar volumetric modulated arc therapy (VMAT) technique, with two other advanced VMAT techniques.MethodsNine patients with ONSMs were re-planned using three radiotherapy techniques: HA employing four preconfigured noncoplanar partial arcs on the Varian TrueBeam, a two-arc coplanar VMAT on the Varian TrueBeam (TB-VMAT), and a two-arc coplanar VMAT on the Varian Halcyon (HAL-VMAT). All treatment plans aimed to deliver 50.4 Gy in 28 fractions to the planning target volume (PTV) while minimizing dose to OARs. The planning process began by applying identical preset optimization templates for each plan, followed by iterative refinements of objectives and priorities to accommodate individual plan requirements. All plans were normalized to ensure that 100% of the prescription dose covered 95% of the PTV. Dosimetric evaluation included PTV metrics (D98%, Dmean, Dmax, and Dmin), the Paddick Conformity Index (PCI), the International Commission on Radiation Units and Measurements Report 83 (ICRU-83) homogeneity index (HI), the gradient index (GI), and doses to OARs for each technique. Statistical significance was assessed using the Wilcoxon signed-rank test with a p-value threshold of < 0.05.ResultsHA plans demonstrated superior dosimetric indices for PTV, as indicated by the highest D98% (50.24 ± 0.05 Gy) and the lowest Dmax (53.20 ± 0.23 Gy), HI (0.04 ± 0.00), and GI (3.56 ± 0.58) values (p < 0.05). These results indicated superior target coverage and a more homogeneous dose distribution. Furthermore, HA plans achieved the lowest maximum dose values for the following OARs: lenses, hippocampi, contralateral optic nerve, and contralateral retina (p < 0.05), thereby optimally sparing these critical structures. No significant differences were observed across techniques regarding Dmean, Dmin, PCI, or maximum dose to the ipsilateral optic nerve, ipsilateral retina, and optic chiasm.ConclusionsHA plans demonstrated superior dosimetric performance, ensuring adequate target coverage, reduced PTV hotspots, and better OAR protection compared to coplanar VMAT plans on the Varian TrueBeam and Halcyon. These advantages suggest that